2018
DOI: 10.1248/bpb.b17-00364
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Reduces Intracellular and Extracellular β-Amyloid in iPS Cell-Derived Alzheimer’s Disease Model Neurons

Abstract: Alzheimer's disease (AD) is the most common cause of dementia, with progressive memory impairment. Recently, neprilysin, a β-amyloid (Aβ)-degrading enzyme has become featured as a drug target for AD. Previously, we identified nobiletin from citrus peels as a natural compound possessing anti-dementia activity. In addition, we demonstrated that nobiletin improved memory in memory-impaired animals and, further, that Aβ levels were markedly decreased in the brains of these animals. We demonstrated in vitro that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Previous studies have shown that NOB has strong antimicrobial, antioxidant, anti-proliferative, anti-inflammatory, and anti-dementia activities [26,[30][31][32][33][34][35]. Convincing evidence has shown that NOB promotes healthy aging in aged male mice with regular or high-fat diets, which works against metabolic disorders and aging-related energy imbalance, including restoring glucose homeostasis, promoting energy expenditure, cold tolerance and circadian activity, optimizing mitochondrial respiratory chain complexes (MRCs) activity and architecture in aged skeletal muscle, and regulating cholesterol and bile acid metabolism [27,36]. In this study, we further explored whether NOB has an effect on aging using the short-lived model organism, C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NOB has strong antimicrobial, antioxidant, anti-proliferative, anti-inflammatory, and anti-dementia activities [26,[30][31][32][33][34][35]. Convincing evidence has shown that NOB promotes healthy aging in aged male mice with regular or high-fat diets, which works against metabolic disorders and aging-related energy imbalance, including restoring glucose homeostasis, promoting energy expenditure, cold tolerance and circadian activity, optimizing mitochondrial respiratory chain complexes (MRCs) activity and architecture in aged skeletal muscle, and regulating cholesterol and bile acid metabolism [27,36]. In this study, we further explored whether NOB has an effect on aging using the short-lived model organism, C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…The development of iPSC technologies provides the attractive possibility of using differentiated human cells as platforms for drug and mutagenesis screening, reviewed by Elitt and colleagues [180]. Multiple small-scale compound screens using differentiated neuronal subtypes have already targeted disease-related pathways in AD [39,[181][182][183][184], Parkinson's Disease [185], Huntington's Disease [186], and frontotemporal dementia [187]. A recent effort screened over 1600 compounds for reductions of tau phosphorylation in FAD neurons, identifying numerous hits and ultimately moving forward our understanding of the biology underlying p-tau accumulation [188].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…38,39 Nobiletin reduced intracellular and secreted Ab in hIPSC-derived neurons with an fAD-associated presenilin-1 mutation. 40 The observed protherapeutic effect is due to increased expression of the Ab-degrading enzyme, neprilysin. 40 Similarly, apigenin, the polyphenolic compound found in celery, parsley, and artichoke, exhibited neuroprotective effects in hIPSC-derived sAD and fAD neurons.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…40 The observed protherapeutic effect is due to increased expression of the Ab-degrading enzyme, neprilysin. 40 Similarly, apigenin, the polyphenolic compound found in celery, parsley, and artichoke, exhibited neuroprotective effects in hIPSC-derived sAD and fAD neurons. 41 Apigenin's anti-inflammatory properties reduced nitric oxide production, increased neurite length, and rescued cell viability.…”
Section: Alzheimer's Diseasementioning
confidence: 99%